Harmonization of proton treatment planning for head and neck cancer using pencil beam scanning: first report of the IPACS collaboration group. (2nd December 2019) - Stock, Markus; Gora, Joanna; Perpar, Ana; Georg, Petra; Lehde, Alexander; Kragl, Gabriele; Hug, Eugen; Vondracek, Vladimir; Kubes, Jiri; Poulova, Zuzana; Algranati, Carlo; Cianchetti, Marco; et al.
Abstract: Background and purpose: A collaborative network between proton therapy (PT) centres in Trento in Italy, Poland, Austria, Czech Republic and Sweden (IPACS) was founded to implement trials and harmonize PT. This is the first report of IPACS with the aim to show the level of harmonization that can be achieved for proton therapy planning of head and neck (sino-nasal) cancer. Methods: CT-data sets of five patients were included. During several face-to-face and online meetings, a common treatment planning protocol was developed. Each centre used its own treatment planning system (TPS) and planning approach with some restrictions specified in the treatment planning protocol. In addition, volumetric modulated arc therapy (VMAT) photon plans were created. Results: For CTV1, the average Dmedian was 59.3 ± 2.4 Gy(RBE) for protons and 58.8 ± 2.0 Gy(RBE) for VMAT (aim was 56 Gy(RBE)). For CTV2, the average Dmedian was 71.2 ± 1.0 Gy(RBE) for protons and 70.6 ± 0.4 Gy(RBE) for VMAT (aim was 70 Gy(RBE)). The average D2% for the spinal cord was 25.1 ± 8.5 Gy(RBE) for protons and 47.6 ± 1.4 Gy(RBE) for VMAT. The average D2% for chiasm was 46.5 ± 4.4 Gy(RBE) for protons and 50.8 ± 1.4 Gy(RBE) for VMAT, respectively. Robust evaluation was performed and showed the least robust plans for plans with a low number of beams. Discussion: In conclusion, several influences on harmonization were identified: adherence/interpretation to/of the protocol, available technology, experience in treatment planning and use of different beam arrangements. In future, all OARs that should be included in the optimization need to be specified in order to further harmonize treatment planning.